Air pollution, dementia, and lifespan in the socio-economic gradient of aging: perspective on human aging for planning future experimental studies - Finch, Caleb E. (Frontiers in Aging, 2023)
Air pollution (AirPoll) accelerates human aging, as assessed by increased adult mortality and earlier onset of cardiovascular diseases, and dementia. Socio-economic strata (SES) of wealth and education have parallel differences of mortality and these diseases. Children from impoverished homes differ in brain development at birth and in risk of early fat excess and hypertension. To further enhance the healthspan, biogerontologists may consider a wider range of environmental exposures from gestation through later life morbidity that comprise the Gero-Exposome. Experimental studies with rodents and nematodes document shared transcriptional responses to AirPoll. In rodents, AirPoll exposure activates gene systems for body-wide detoxification through Nrf2 and NFkB transcription factors that mediate multiple aging processes. Gestational environmental factors include maternal diet and exposure to AirPoll and cigarette smoke. Correspondingly, gestational exposure of mice to AirPoll increased adult body fat, impaired glucose clearance, and decreased adult neurogenesis in the hippocampus, a brain region damaged in dementia. Nematode larvae also respond to AirPoll with Alzheimerrelevant responses. These experimental approaches could identify to interventions for expanded human health and longevity across SES gradients.